Diffusive dispersal in a growing ungulate population: guanaco expansion beyond the limits of protected areas - Iranzo Sanz, Esperanza (2018)
Growth of wild ungulate populations within protected areas can cause an expansion towards surrounding non-protected areas and lead to conflicts with human activities. The spatial and demographic structure of colonizing populations inform about their state and potential trends, since the initial colonization by dispersing individuals precedes the establishment of a population with potential for further growth and expansion. Once colonization has succeeded, the spatial pattern of animal abundance is associated with intra- and interspecific interactions and environmental factors (e.g., habitat and food availability) and the population shows similar demographic features throughout the whole occupation area, which has been called a diffusive dispersal pattern. Here, we analyze the current status of colonization by a guanaco population of ranches surrounding a protected area in Chilean Patagonia with data gathered along three consecutive years. We thus compared animal abundance and social structure between the protected and unprotected areas and evaluated throughout the whole area the effect of environmental factors on guanaco abundance, proportion of family groups, and reproductive success. Guanaco abundance significantly declined with increasing distance from the center of the local distribution and marginally with predation risk. Moreover, social structure showed only minor differences between areas, pointing to a diffusive dispersal pattern. These results suggest that the population is already well established and has the potential to grow and continue its expansion. The case exemplifies a challenging outcome of successful animal conservation, and it presents a useful approach to evaluate the state of wild ungulate populations colonizing new areas.